Pleiotropic functions of the tumor- and metastasis-suppressing matrix metalloproteinase-8 in mammary cancer in MMTV-PyMT transgenic mice. Issue 1 (December 2015) - Decock, Julie; Hendrickx, Wouter; Thirkettle, Sally; Gutiérrez-Fernández, Ana; Robinson, Stephen; Edwards, Dylan
Abstract Introduction Matrix metalloproteinase-8 (MMP-8; neutrophil collagenase) is an important regulator of innate immunity that has oncosuppressive actions in numerous tumor types. Methods We have intercrossedMmp8 -null mice with the Polyoma virus middle T oncogene-driven (MMTV-PyMT) mouse model of mammary cancer to explore the effects of loss of MMP-8 on the incidence and progression of mammary carcinomas. Results In this aggressive mouse model of breast cancer, loss of MMP-8 accelerated tumor onset even further, such that 90% ofMMTV-PyMT ;Mmp8 -null female mice were tumor-bearing at the time of weaning. Throughout the 14 weeks of the model, tumor burden increased in homozygousMmp8 -null mice compared toMmp8 -wild-type and -heterozygote animals. Likewise, lung metastasis dramatically increased in theMMTV-PyMT ;Mmp8 -null mice. Immunohistochemistry revealed that tumors in wild-type, Mmp8 -heterozygotes and -null animals had similar vascular density at 8 weeks, but at 10 weeksMmp8 -wild-type tumors had a lower vascularity than their heterozygote and null counterparts. No differences in macrophage infiltration were apparent throughout primary tumor development, though at 10 weeks a drop in neutrophil infiltrates was observed inMmp8 -wild-type tumors. Using quantitative real-time RT-PCR, we tracked the expression of the entireMmp andTimp gene families, observing a significant decrease inMmp3 expression inMmp8 -null tumors compared to wild-type and heterozygotes throughout the time course of the model, which was confirmed at the protein level. Conclusions These findings provide novel insight into the suppressive action of MMP-8 on mammary tumorigenesis and metastasis, and indicate that the loss of MMP-8 likely has pleiotropic effects on innate immunity and angiogenesis that are reflected in changes in the protease web.